Banking soundness and monetary policy issues and experiences in the global economy: papers presented at the Seventh Seminar on Central Banking Washington, D.C. January 27-31, 1997 - Enoch, Charles; Green, John Huss; IMF Institute; International Monetary Fund (Washington : IMF Institute and Monetary and Exchange Affairs Dept., International Monetary Fund, 1997)
This volume brings together contributions on a wide variety of banking soundness issues. The contributions range from papers focusing on theoretical aspects of ensuring banking system soundness to others presenting practical lessons from individual country experiences.
papers presented at the Seventh Seminar on Central Banking Washington, D.C. January 27-31, 1997.
Includes bibliographical references.
aia 12/8/16
Keywords: Banks and banking; Banks and banking -- State supervision -- Congresses; Monetary policy; Banks and banking, Central